Amphiphilic Perylene-Calix[4]arene Hybrids: Synthesis and Tunable Self-Assembly - Rodler, Fabian; Schade, Boris; Jaeger, Christof M.; Backes, Susanne; Hampel, Frank; Boettcher, Christoph; Clark, Timothy; Hirsch, Andreas (Journal of the American Chemical Society, 2015)
The first highly water-soluble perylene-calix[4]arene hybrid with the calixarene scaffold acting as a structure-determining central platform is presented. In this tetrahedrally shaped amphiphilic architecture the hydrophilic and hydrophobic subunits are oriented at the opposite side of the calixarene platform. The hydrophobic part contains the two perylene diimide moieties, which enable strong pi-pi interactions in self-assembly processes. Two hydrophilic Newkome-type dendrons provide sufficient water solubility at slightly basic conditions. The tetrahedrally shaped amphiphile displays an unprecedented aggregation behavior down to concentrations as low as 10(-7) mol L-1. The intriguing self-assembly process of the compound in water as well as under changed polarity conditions, achieved by addition of THF, could be monitored by the complemented use of cryogenic transmission electron microscopy (cryo-TEM), UV-vis spectroscopy, and fluorescence spectroscopy. Molecular-dynamics and molecular modeling simulations helped in understanding the interplay of supramolecular and optical behavior.

Naphthalenebisimides as photofunctional surfactants for SWCNTs - towards water-soluble electron donor-acceptor hybrids - Dirian, Konstantin; Backes, Susanne; Backes, Claudia; Strauß, Volker; Rodler, Fabian; Hauke, Frank; Guldi, Dirk Michael; Hirsch, Andreas (Chemical Science, 2015)
A water soluble naphthalenebisimide derivative (NBI) was synthesized and probed to individualize, suspend, and stabilize single wall carbon nanotubes (SWCNTs). Besides a comprehensive photophysical and electrochemical characterization of NBI, stable suspensions of SWCNTs were realized in buffered D2O. Overall, the dispersion efficiency of the NBI surfactant was determined by comparison with naphthalene based references. Successful individualization of SWCNTs was corroborated in several microscopic assays. In addition, emission spectroscopy points to the strong quenching of SWCNT centered band gap emission, when NBIs are immobilized onto SWCNTs. The origin of the quenching was found to be strong electronic communication, which leads to charge separation between NBIs and photoexcited SWCNTs, and, which yields reduced NBIs as well oxidized SWCNTs. Notably, electrochemical considerations revealed that the energy content of these charge separated states is one of the highest reported for SWCNT based electron donor-acceptor hybrids so far.

Nickel oxide nanostructured electrodes towards perylenediimide-based dye-sensitized solar cells - Feihl, Sebastian; Costa Riquelme, Rubén Dario; Pflock, Stephan; Schmidt, Cordula; Schönamsgruber, Jörg; Backes, Susanne; Hirsch, Andreas; Guldi, Dirk Michael (RSC Advances, 2012)
In this work, we have realized nickel oxide (NiO) electrodes that serve as photocathodes in p-type dye-sensitized solar cells (p-DSSCs) sensitized by dendronized perylenediimides (PDIs). To this end, two different approaches in terms of preparing NiO nanoparticle pastes were pursued to fabricate mesoporous electrodes on conductive fluorine doped tin oxide (FTO) glass substrates. Firstly, commercially available NiO nanoparticles were dispersed in a mixture of ethanol and terpineol. Here, in order to obtain a mesoporous network two types of ethylcelluloses (EC), that is, EC 5-15 and 30-50 mPa s, were added in 1:1 weight ratios. Following the evaporation of ethanol, the resulting pastes were spread on FTOs by doctor blading and calcinated at different temperatures. Importantly, the calcination temperature evolved as a crucial aspect in developing efficient electrodes. Nevertheless, the visual appearance of these NiO electrodes prompts a fairly heterogeneous coverage. To circumvent the aforementioned problem, a second approach en route to homogenous electrodes was investigated. In that particular case, commercial NiO nanoparticles were mixed with a mixture of EC 5-15 and 30-50 mPa s at a 1:1 weight ratio, with triacetin as a plasticizer in ethanol. In doing so, pastes containing 7 wt% EC, 3 wt% triacetin, and 3 to 20 wt% NiO nanoparticles were prepared. Most importantly, scanning electron microscopy (SEM) images corroborated the fact that the resulting electrodes revealed a dense coverage on FTOs. In addition, further characterizations ranging from UV/Vis transmission spectroscopy and conductivity measurements to Barrett-Joyner-Halenda (BJH) pore size and volume analysis were carried out. In the final step, the applicability of the new NiO photoelectrodes for p-DSSCs was successfully demonstrated by utilizing two types of PDIs, namely a symmetric 1 and a non-symmetric dendronized 2. Key aspects such as time dependence of dye uptake, hole lifetime and resistance features of the electrodes under operation conditions were investigated. © 2012 The Royal Society of Chemistry.